Infantile acute megakaryoblastic leukaemia with T(1:22) in a non-down syndrome child. - Nurasyikin Y; shenaz SK; Suria AAA; Azma RZ; zarina AL; Hamidah A; Salwati S; Zubaidah Z; Aminah NH (Penerbit UKM, 2012)
Megakaryoblastic leukaemia is the commonest form of leukaemia occuring in Down syndrome infants. However, it’s subtype with translocation t(1;22)(p13;q13)is uncommon comprising <1% of all cases and reported to exclusively occur in infant without Down syndrome. It has a female predominance and carries apoor prognosis. We described this rare form of leukaemia in a 9-month-old girl who presented with bruises, massive hepatosplenomegaly and multiple cervical and inguinal lymphadenopathy. The blood film showed severe anaemia with ovalostomatocytosis, thrombocytopenia and mild leucocytosis. The bone marrow aspirate showed numerous blasts showing high nuclear-cytoplasmic ratio and agranular cytoplasm with cytoplasmic blebs. Peroxidase staining was negative. The immunophenotyping of the blasts showed positive expression of CD117, CD13, CD33 and CD61 which confirmed the diagnosis of acute megakaryoblastic leukaemia. Interestingly, the cytogenetic finding of translocation t(1;22) which is most common in acute megaloblastic leukaemia in infants without Down syndrome was found in this case. She received the AML trial 15 ADE protocol chemotherapy regime and developed severe neutropenic sepsis and respiratory distress requiring ventilatory support and granulocyte colony stimulating factor (G-CSF). She recovered wellmafter the first course of chemotherapy and was discharged. Unfortunately, she was not brought in for follow-up chemotherapy and presented a few months later with relapsed AML. She was re-started on ADE protocol and currently is on oral thioguanine for maintenance therapy.